Food value chains configurations and resilience of rural mountain communities: three dairy business models in central Apennines (Italy) - Belliggiano, Angelo; Ievoli, Corrado; Bispini, Sara; Conti, Mauro (Frontiers in Sustainable Food Systems, 2024)
The research was held in “Alto Molise,” a mountain area embedded in a small region of southern Italy, focusing on the dairy value chain of the “caciocavallo cheese,” historically rooted in the socio-ecological system of the mountain reference landscape. The local production system connects the environmental setting (i.e., permanent grasslands and meadows), livestock farming skills (linked to the pastoral heritage like traditional transhumance practice), the production of dairy goods (still partially made with craft techniques), and socio-cultural heritage (e.g., mountain farming and artisan culture). In particular, the focal value chain of caciocavallo cheese in Alto Molise involves local natural and socio-cultural resources, it is also linked to other value chains (such as tourism and meat production), and its development can contrast socio-environmental depletion of the territorial capital in Alto Molise, according to the different business models operating in the value chain. This chain is organized around the cheesemakers who hold a market power compared to others, even though the breeders are the ones to rely on the uniqueness of the natural resource units. This form of governance leads to high value creation but with a low efficiency of value distribution. Indeed, the market structure and power relations for each stage of the chain process resulted in oligopsony for milk production and milk collection, while the milk processing has the characteristic of monopolistic competition. The analysis resulted in a strong weakness of the farmers, which may threaten the very economic sustainability of the value chain. In order to represent the situation, the research identified three ideal types of business models to outline their interaction with the socio-ecological system at different stages of the value chain (production, processing, retailing, and consumption) and their impact on territorial capitals and on the resilience of mountain rural communities, including adaptation to climate change and reverse depopulation: model A—Network variant: cheesemakers use only local raw milk establishing fair economic and social collaboration with local breeders; Model B—Market variant: cheesemakers use pasteurized milk produced in the area, in Italy or in the UE for a more “industrialized” production process, model C—Autonomy variant: breeders/milk producers are also cheesemakers in this case. At the production level, the environmental capital and the socio-cultural capital and intangible cultural heritage enter the value chain mainly through business models A and C. Business model B allows this connection and valorization only based on the specialization and dairy enterprise reputation, connects with territorial capital of the production stage of experiential tourism and meat value chains, and the actors as processors and family businesses, but not on the territorial capital of the production stage as landscape based on the interaction of agriculture with the natural habitats. This implies a shift in the production model toward a more industrialized one with raw materials from outside the area and stable farming models with common permanent grassland and meadows less engaged in the chain.